The Influence of Promotion and Brand Image on Repurchase Intention at Kopi Kenangan Ruko Hayam Wuruk, Kota Kediri - Putri, Sindy Dwinta; Heryanto, Budi; Prasetyo, Priyo (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2025)
This study analyzes the influence of promotion and brand image on consumers’ repurchase intention at the Kopi Kenangan outlet in Ruko Hayam Wuruk, Kediri City. The background of this research is based on the growing competition in the coffee business and the importance of promotional strategies and brand image in maintaining customer loyalty. This research uses a quantitative approach with survey methods through questionnaires distributed to 100 respondents who are customers of Kopi Kenangan. The sampling technique used is purposive sampling. Data analysis was conducted using multiple linear regression with the help of SPSS software. The results of the study show that partially, the promotion variable has a significant effect on repurchase intention, as does brand image, which also significantly affects repurchase intention. Simultaneously, both independent variables positively and significantly influence repurchase intention. Therefore, it can be concluded that attractive promotional strategies and a strong brand image play a vital role in encouraging consumers to make repeat purchases at Kopi Kenangan outlets. Keywords: Promotion, Brand Image, Repurchase Intention, Kopi Kenangan, Marketing Strategy